2023
DOI: 10.1039/d3ta01418e
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating water oxidation on BiVO4 photoanodes via surface modification with Co dopants

Abstract: Despite the vast investigations on improving the photoelectrochemical performance of BiVO4 for water splitting, charge recombination in the near-surface region remains a challenge. In this study, we showed that the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…99 EPR can detect OVs, both at the surface and in the bulk medium in a wide range of substrates, e.g. titanium-based catalysts (TiO 2 , SrTiO 3 ), 12,68,75,83,100,101 bismuth-based catalysts (Bi 24 O 31 Br 10 , BiOCl, Bi 2 O 3 , BiVO 4 , BiO x , Bi 5 O 7 Br), 102–105 tungsten-based catalysts (WO 3 , W 18 O 49 ), 106 SnO 2 , 107,108 CuCr-LDH, 109 CuO, 110 Fe 2 O 3 , 111 Cu 2 O@CuNiMo 112 and CuZnAl-LDH. 79 OVs usually give rise to an isotropic, single-line EPR signal centered at around g ≈ 2.0.…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%
“…99 EPR can detect OVs, both at the surface and in the bulk medium in a wide range of substrates, e.g. titanium-based catalysts (TiO 2 , SrTiO 3 ), 12,68,75,83,100,101 bismuth-based catalysts (Bi 24 O 31 Br 10 , BiOCl, Bi 2 O 3 , BiVO 4 , BiO x , Bi 5 O 7 Br), 102–105 tungsten-based catalysts (WO 3 , W 18 O 49 ), 106 SnO 2 , 107,108 CuCr-LDH, 109 CuO, 110 Fe 2 O 3 , 111 Cu 2 O@CuNiMo 112 and CuZnAl-LDH. 79 OVs usually give rise to an isotropic, single-line EPR signal centered at around g ≈ 2.0.…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%
“…In addition to these possible solutions, it has been reported that the controlled growth of semiconductors with the help of surface-active reagents can also have an impact on their photocatalytic and PEC activities. 14,15 Surfactants such as polyethylene glycol (PEG), sodium dodecyl sulfide (SDS), thioglycerol (TG), and hexadecyltrimethylammonium bromide (CTAB) are used as stabilizing reagents in order to control the direction and the extent of the particle growth and to manipulate the optical and structural characteristics of the nanomaterials. [16][17][18] In comparison to other surfactants, CTAB is less toxic and cheaper as a capping agent alternative which is significantly utilized for the synthesis of CdS colloidal particles.…”
Section: Introductionmentioning
confidence: 99%
“…With the massive fossil energy consumption and increasing global warming, developing relevant energy storage devices is essential in utilizing sustainable and renewable energy resources. Common energy storage devices include lithium-ion batteries, fuel cells, and supercapacitors . Supercapacitors with the advantages of low cost, high power density, high specific capacity, and long cycling life have been expected to be an emerging generation of rechargeable energy storage devices with bright prospects .…”
Section: Introductionmentioning
confidence: 99%